THE EFFECT OF CLINICAL TEACHING METHOD AND LEARNING STYLE ON CLINICAL NURSING LEARNING OUTCOMES - Ida Zuhroidah; Nurul Huda; Bagus Dwi Cahyono (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2019)
Background: Nursing Academy of Pasuruan has used problem solving method for learning clinical nursing practice. However, there is obstacle in the implementation of the method due to wide variation in implementing the method among field instructors. Theoretically, bedside teaching method can be used for learning activities to improve learning outcomes. Theoretically, students' learning style is associated with learning outcomes.Objective: This study aimed to examine the effect of clinical bedside teaching method and learning style of students on clinical practice outcome among nursing students at the Academy of Nursing.Method: The research method used Quasi-Experimental. The population source was students at the Academy of Nursing, Pasuruan. A sample of 80 students were selected by simple random sampling. Problem solving was used as a comparison method. The data were collected using standard questionnaires, and analyzed by multiple linear regression model.Result: Results indicated that bedside teaching resulted in higher clinical nursing learning outcome than problem solving method (b = 3.5, p < 0.001, CI 95% 2.6 to 4.4). There was no statistically significant effect of learning styles on learning outcomes of nursing clinical practice (p > 0.05).Conclusion: This study concludes that bedside teaching method results in better clinical nursing learning outcome than problem solving method. It is recommended that all faculty members use bedside teaching as the learning strategy to improve learning outcomes in clinical practice. Key words: Bedside Teaching, Problem Solving, Learning Styles, Clinical Practical Learning Outcomes.